2021
DOI: 10.33448/rsd-v10i5.14674
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do treinamento resistido em mulheres com fibromialgia: Um estudo de revisão

Abstract: A fibromialgia é uma síndrome reumática que causa dor musculoesquelética crônica disseminada, por um período maior que três meses, cujos sintomas são dores nos tecidos moles como músculos, tendões ou ligamentos. O objetivo desta revisão foi analisar estudos que avaliaram a influência do treinamento resistido sobre a saúde de mulheres com fibromialgia. Trata-se de uma revisão integrativa de estudos publicados entre 2016 e 2020. A busca e seleção dos estudos foi realizada a partir dos termos: fibromyalgia OR fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Marin Bosch et al showed that moderate-intensity exercise was correlated with increased circulating levels of AEA and increased activity in the caudate nucleus and hippocampus and concluded that AEA stimulates hippocampal and striatal activity and function, thereby enhancing memory for motor sequences. High levels of AEA are associated with improved motor sequence memory (Marin Bosch et al, 2020;Thomas et al, 2016) (Barbosa et al, 2021). Several authors have hypothesized that moderate physical exertion with time between 30-90 minutes/per workout will increase plasma levels of circulating EC which generate a system-wide response to seek, consume, and store energy.…”
mentioning
confidence: 99%
“…Marin Bosch et al showed that moderate-intensity exercise was correlated with increased circulating levels of AEA and increased activity in the caudate nucleus and hippocampus and concluded that AEA stimulates hippocampal and striatal activity and function, thereby enhancing memory for motor sequences. High levels of AEA are associated with improved motor sequence memory (Marin Bosch et al, 2020;Thomas et al, 2016) (Barbosa et al, 2021). Several authors have hypothesized that moderate physical exertion with time between 30-90 minutes/per workout will increase plasma levels of circulating EC which generate a system-wide response to seek, consume, and store energy.…”
mentioning
confidence: 99%